2006
DOI: 10.1242/dev.02689
|View full text |Cite
|
Sign up to set email alerts
|

Threshold response ofC15to the Dpp gradient inDrosophilais established by the cumulative effect of Smad and Zen activators and negative cues

Abstract: Morphogen gradients determine a range of cell fates by specifying multiple transcriptional threshold responses. In the dorsal ectoderm of the Drosophila embryo, a BMP gradient is translated into an activated Smad transcription factor gradient, which elicits at least three threshold responses -high, intermediate and low. However, the mechanism underlying differential response to Dpp is poorly understood, due in part to the insufficient number of well-studied target genes. We analyzed the regulation of the C15 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…In Drosophila, the transcripts and proteins of all three genes are expressed throughout the developing amnioserosa, albeit in different time windows. Extraembryonic C15 expression starts in the blastoderm and continues until after germband retraction (25,26). Extraembryonic pnr expression starts in the blastoderm and fades during the extended germband stage (stage 10) (27).…”
Section: Phenotypic Effects Of Zen Rnai In Megaselia and Episyrphusmentioning
confidence: 99%
“…In Drosophila, the transcripts and proteins of all three genes are expressed throughout the developing amnioserosa, albeit in different time windows. Extraembryonic C15 expression starts in the blastoderm and continues until after germband retraction (25,26). Extraembryonic pnr expression starts in the blastoderm and fades during the extended germband stage (stage 10) (27).…”
Section: Phenotypic Effects Of Zen Rnai In Megaselia and Episyrphusmentioning
confidence: 99%
“…S7 in the supplementary material), although it was weaker than the previously published intronic C15 enhancer (Fig. 4A, fragment 3) (Lin et al, 2006).…”
Section: Fig 3 Overexpression Of Ladybird and C15 Represses Evementioning
confidence: 51%
“…S3 in the supplementary material, Apis). In Drosophila, C15 is expressed in the dorsal ectoderm (Lin et al, 2006) and in the leg discs, where it works with aristaless to pattern the distal tip of the leg (Campbell, 2005). Drosophila C15 is additionally expressed in a subset of dorsal mesodermal cells outside the cardiac field (M. Frasch, personal communication).…”
Section: Apismentioning
confidence: 99%
See 1 more Smart Citation
“…Dpp signaling, which activates the transcription factors Mothers against dpp (Mad), and Zen induce dorsal ectodermal fate (Raftery et al 1995;Rusch and Levine 1997;Lin et al 2006). We therefore analyzed the occupancy of Mad and Zen in gd 7 embryos and found that their occupancy at both active DEEs and uninduced MEs was also significantly higher than at the closed control regions (Fig.…”
Section: Resultsmentioning
confidence: 97%